Development of Kahoot-Based Learning to Improve the Effectiveness of Language Learning in Schools - Amalina, Arin; Falah, Berlina Adinul Quyum Al (JOURNAL OF TECHNOLOGY, EDUCATION & TEACHING (J-TECH), 2025)
This study explores the use of Kahoot, a game-based learning platform, in enhancing the effectiveness of language learning in schools. Using meta-analysis and literature review methods, this research aims to analyze the impact of Kahoot on student motivation, engagement, and learning outcomes. The findings indicate that the implementation of Kahoot in the context of language learning can significantly enhance student engagement and learning outcomes, providing insights for the development of more interactive teaching methods.